Three-Dimensional Analysis of Garden Bench Design on Pressure Distribution Using Finite Difference Method Approach - Sang Narendra Wyatt; Ahmad Faisal Ridho; Khaira Zatinnayyara; Muhammad Hamzah Hanan; Muhammad As’ad Alquroimi; Ridwan Ridwan (Journal of Industrial and Mechanical Engineering, 2023)
A park bench is one of the facilities that can be found in parks, and it serves the purpose of providing park users with a place to rest or socialize with one another. Consequently, a design that is created with the use of computer-aided design (CAD) is the requirement. Following that, a Computer Aided Engineering (CAE) stage is required. This stage is necessary since it assists in the execution of pressure simulations. Pressure simulation is essential in order to guarantee that the product is robust enough. This research was carried out to test the pressure strength of a park bench by applying pressure from the top of the bench with a minimum load of 1,233 Mpa and a maximum load of 1,246 Mpa, resulting in the surface of the bench experiencing different force pressures and the part of the bench surface that received the most significant pressure was the middle of the bench. The approach known as the Finite Difference Method was utilized in order to carry out modeling for three dimensions.